Technological prospection of solid waste gasification applications in Brazil - Silva, Diogo Santos (2023)
Environmental issues weigh heavily on international economic relations with demands for stricter environmental regulations for the deforestation of forest areas and the generation of urban solid waste (USW). These demands drive research in the area of USW to reduce the waste volume and to its use in various fields such as power generation. In 2020, the legal milestone of the National Solid Waste Policy (NSWP) in Brazil was updated, opening space for private initiative in the management of systems related to USW. This work aims to carry out a technological prospection on gasification developed in Brazil using translational research and databases from CAPES, Web of Science, and ESPACENET portals to verify research incentives in universities, public and private, from 1984 to 2022. The search strategy first maps the search for dissertations (master's) and theses (doctoral) documents, called non-patented literature on biomass gasification, and it verifies the relationship with the production of articles in the area, and secondly, it correlates with the production of gasification patent documents. Implementation trends and factors that influenced gasification research were analyzed which generated 357 academic documents (thesis and dissertation), petitioners of patent applications and granted patents in Brazil, and academic research that reached society in the format of 189 articles and one patent.